Teoria do prospecto e a tendência à aversão ao risco - Trucolo, Celso Fernandez (FES - Faculdade de Estudos Sociais, 2022)
Developed by Kahneman and Tversky (1979), Prospect Theory, or Perspective Theory analyzed the investors’ behavior on decision-making process under risk. According to the authors, psychosocial factors exert influence over the decision process, because of the bounded rationality of the individuals. Furthermore, economic agents have a tendency to avoid losses in some economic scenarios, to the detriment of the resulting gains. According to the authors, unlike Utility Theory, which is based upon the analysis of the axioms obeyed by reasonable people, Prospect Theory’s goal is to verify the real behavior of consumers, investors, or economic agents in a free market context. To sum it up, the present article’s purpose is to analyze the behavior of the students of a Federal University of Brazil North Region, when confronted with choices under risk, in the context of the certainty, reflection and isolation effects proposed by Kahneman’s and Tversky’s Prospect Theory (1979). Therefore, the research is presented in the form of a quali-quantitative approach, via an adapted version of Kahneman’s and Tversky’s questionnaire, applied to 78 students in order to verify Prospect Theory’s effects. The results were compatible with the original study, as well as other similar studies over the country, which means, the individuals are unwilling to take risks regarding to their gains, inclined to take risks regarding losses, and susceptible to isolation effect regarding gains and losses.